Studies on the natural history of yellow fever in Trinidad - Tikasingh, Elisha S., ed. (Caribbean Epidemiology Centre Port of SpainTT, 1991)
Records the history of yellow fever in Trinidad as well as the origins and some of the work of the Caribbean Epidemiology Centre in the region.